Neuropsychological evidence distinguishing object selection from action (effector) selection. - Riddoch, M; Humphreys, G; Edwards, MG (2000)
We report two sets of data on object and action selection in a patient, ES, with an impaired ability to make task-based actions to objects. In simple action tasks, ES often made familiar actions to objects rather than the action appropriate to the task rule. We show that, despite having impaired selection of action, ES was able to select the target for action (based on salient perceptual differences). Relatively good object selection occurred even when the distractor had a stronger learned response than the target. In addition we show that distractors close to the path of action to a target can compete for, but are rejected from, selection along with any concurrently activated response. Suppression of an activated response improved performance, when the response would have been inappropriate to the task.